Impact of successive sugarcane harvests and trash management practices on soil microbiological properties - Pupin, Breno [UNESP]; Nahas, Ely [UNESP] (CSIRO Publishing, 2011)
Sugarcane culture is replanted after five-eight successive harvests and intensely fertilised and mechanised. The influence on bacteria (total, nitrifying, denitrifying), fungi, microbial biomass-C, and dynamic processes (respiratory activity, N mineralisation, potential nitrification, P-solubilising activity) and enzymatic activities (dehydrogenase, urease, phosphatase) was studied for six successive harvests of the crop. The straw of the second and third harvest was burned. Soil microbial counts and activities were reduced after successive harvests. Fungi counts, N mineralisation, potential nitrification, and the P-solubilising, urease, and phosphatase activities decreased gradually from the first harvest to the third, increased again after the fourth, and then decreased again. Total, nitrifying, and denitrifying bacteria and fungi counts decreased, on average, 55, 22, 17, and 77%, respectively, in the sixth harvest in relation to the first. Reductions also occurred in microbial biomass-C (43%), respiratory activity (39%), N mineralisation (35%), potential nitrification (40%), and P-solubilising activity (35%). Reductions were observed in dehydrogenase (58%) and urease (36%) activities, but not in phosphatase activity. Successive sugarcane harvests may significantly influence microbial populations and activities, with harmful consequences to the C, N, and P cycles, and may decrease crop productivity.
Keywords: Bacteria; dehydrogenase; fungi; potential nitrification; respiratory activity; urease